Application of 3D imaging and analysis techniques for the study of food plant cellular deformations during drying. Issue 5 (4th April 2018) - Rathnayaka, C. M.; Karunasena, H. C. P.; Senadeera, W.; Gu, Y. T.
ABSTRACT: In this investigation, novel 3D imaging and image-analysis tools have been used to observe the deformations of food-plant tissues and single cells during convective air drying at 70°C. A comprehensive investigation was performed to qualitatively and quantitatively analyze the shrinkage and surface wrinkling of Royal Gala apple parenchyma cellular structure during drying. To study the cellular morphology, 3D contour maps produced by a novel 3D image and surface analysis tool, "Nanovea Expert 3D" were used. ImageJ software was used to quantify the single cell morphological characteristics. During the study, each tissue was observed continuously for the gradual morphological alterations. It was evident that there is a significant reduction of surface roughness during the drying process. In the case of individual cells, the area reduced approximately by 20% and diameter by 11%. This study provides conclusive proof that 3D contour maps and images combined with the 2D microscopic images could be a highly valuable source of information in producing data for the validation of 3D computational plant tissue drying models and simulations.